Metacritique on Bentham and Foucault’s panoptic theories as analytic tools for three modes of digital surveillance - Parreno, June Benedict; Demetrio, Feorillo Petronilo A., III (2024)
Access online through this link: https://www.plarideljournal.org/article/metacritique-on-bentham-and-foucaults-panoptic-theories-as-analytic-tools-for-three-modes-of-digital-surveillance
Keywords: Foucault, Michel, 1926-1984; Bentham, Jeremy, 1748-1832; Electronic surveillance